Rediscovering the Axolotl as a Model for Thyroid Hormone Dependent Development - Crowner, Anne; Khatri, Shivam; Blichmann, Dana; Voss, S. Randal (Frontiers in Endocrinology, 2019)
The Mexican axolotl (Ambystoma mexicanum) is an important model organism in biomedical research. Much current attention is focused on the axolotl’s amazing ability to regenerate tissues and whole organs after injury. However, not forgotten is the axolotl’s equally amazing ability to thwart aspects of tissue maturation and retain juvenile morphology into the adult phase of life. Unlike close tiger salamander relatives that undergo a thyroid hormone regulated metamorphosis, the axolotl does not typically undergo a metamorphosis. Instead, the axolotl exhibits a paedomorphic mode of development that enables a completely aquatic life cycle. The evolution of paedomorphosis allowed axolotls to exploit relatively permanent habitats in Mexico, and preadapted axolotls for domestication and laboratory study. In this perspective, we first introduce the axolotl and the various meanings of paedomorphosis, and then stress the need to move beyond endocrinology-guided approaches to understand the axolotl’s hypothyroid state. With the recent completion of the axolotl genome assembly and established methods to manipulate gene functions, the axolotl is poised to provide new insights about paedomorphosis and the role of thyroid hormone signaling in development and evolution.